COOL — A Generic Reasoner for Coalgebraic Hybrid Logics (System Description) - Gorin, Daniel; Pattinson, Dirk; Schröder, Lutz; Widmann, Florian; Wißmann, Thorsten (Automated Reasoning, 2014)
We describe the Coalgebraic Ontology Logic solver Cool, a generic reasoner that decides the satisfiability of modal (and, more generally, hybrid) formulas with respect to a set of global assumptions-in Description Logic parlance, we support a general TBox and internalize a Boolean ABox. The level of generality is that of coalgebraic logic, a logical framework covering a wide range of modal logics, beyond relational semantics. The core of Cool is an efficient unlabelled tableaux search procedure using global caching. Concrete logics are added by implemening the corresponding (one-step) tableaux rules. The logics covered at the moment include standard relational examples as well as graded modal logic and Pauly's Coalition Logic (the next-step fragment of Alternating-time Temporal Logic), plus every logic that arises as a fusion of the above. We compare the performance of Cool with state-of-the-art reasoners. © 2014 Springer International Publishing Switzerland.
UnivIS-Import:2015-04-17:Pub.2014.tech.IMMD.profes_1.coolag